Evaluating the influence of differences in methodological approach on metabolic thresholds and fat oxidation points relationship. Issue 1 (2nd January 2021) - Nikolovski, Zoran; Barbaresi, Silvia; Cable, Tim; Peric, Ratko
Abstract: In this study, we aimed to determine the exercise intensities eliciting the highest (FATmax ) and the lowest (FATmin ) fat oxidation rate in male cyclists and to compare these intensities with their individual aerobic (AeT) and anaerobic (AnT) thresholds, respectively. Twenty-two moderately trained male cyclists performed a 2-min stage graded exercise test until exhaustion using breath-by-breath gas analysis to determine maximal oxygen consumption (VO2max ). The fat oxidation rate was calculated using a stoichiometric equation, with metabolic thresholds being determined by ventilatory gas analysis. In the present group of subjects, FATmax was found at a 21.34 ± 3.64 ml·kg −1 ·min −1 corresponding to 45.05 ± 7.68% VO2max . AeT occurred at an exercise intensity of 22.15 ± 4.84 ml·kg −1 ·min −1, matching 46.76 ± 10.24% VO2max . AnT and FATmin were located at intensities equivalent to 32.56 ± 5.52 ml·kg −1 ·min −1 and 32.30 ± 5.35 ml·kg −1 ·min −1 which corresponded to 68.74 ± 11.65 and 68.19 ± 11.29% VO2max, respectively. The correlation between FATmax and AeT was strong ( r = 0.80, p < 0.05). No statistical difference was observed between FATmin and AnT ( r = 0.99, p < 0.05). The strong relationship between observed indices can be used to provide a more tailored exercise approach.